Dopaminergic polymorphisms associated with medication responsiveness of gait in Parkinson's disease. (March 2018) - Miller, Nathaniel S.; Chou, Kelvin L.; Bohnen, Nicolaas I.; Müller, Martijn L.T.M.; Seidler, Rachael D.
Abstract: Background: Gait dysfunction is a common symptom of Parkinson's disease that can cause significant disability and put patients at risk for falls. These symptoms show variable responsiveness to dopaminergic therapy. Objective: To determine whether dopaminergic (rs1076560 DRD2 G > T and rs4680 catechole- o -methyltranspherase ( COMT ) Val158Met) or brain derived neurotrophic factor (rs6265 BDNF Val66Met) genetic polymorphisms are associated with gait function and medication responsiveness in Parkinson's disease. Method: Gait function was evaluated on two days for patients (ON and OFF medication in a counterbalanced fashion) and a single session for controls. Investigators were blinded to genotype during data collection. Associations between genotype and medication responsiveness were analyzed using mixed model ANOVAs. A priori hypotheses were tested using GAITRite ® electronic mat spatiotemporal gait parameters including step length, step width, velocity, portion of double and single support per gait cycle, and variability of these measures ON and OFF medication. Results: We found that the DRD2 polymorphism, but neither COMT nor BDNF, was consistently associated with gait function and medication responsiveness in the patients. Specifically, Parkinson's disease patients with reduced striatal D2 expression ( DRD2 T allele carriers) had worse gait dysfunction and showed greater dopamine responsiveness of gait function compared to patients who were homozygous for the G allele. There was no effect of any of the genetic polymorphisms on gait for controls. Conclusions and relevance: The findings suggest that genetic subgrouping, in particular for DRD2, may be used to identify Parkinson's disease patient subgroups that are more dopamine responsive for gait function. Highlights: DRD2 genetic polymorphism associates with gait in patients with Parkinson's disease. Patients carrying the DRD2 T allele show more gait improvements ON medication. COMT and BDNF genetic polymorphisms did not associate with treatment response.